2023
DOI: 10.1162/coli_a_00462
|View full text |Cite
|
Sign up to set email alerts
|

Transformers and the Representation of Biomedical Background Knowledge

Abstract: Specialised transformers-based models (such as BioBERT and BioMegatron) are adapted for the biomedical domain based on publicly available biomedical corpora. As such, they have the potential to encode large-scale biological knowledge. We investigate the encoding and representation of biological knowledge in these models, and its potential utility to support inference in cancer precision medicine - namely, the interpretation of the clinical significance of genomic alterations. We compare the performance of diff… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 46 publications
0
8
0
Order By: Relevance
“…Cao et al [45] showed that predictions from MLM are highly prompt-biased and that, while external context apparently helps the models, its mainly via type guidance or answer leakage. In follow-up works, many domain-specific datasets and original prompting approaches were developed for factual knowledge extraction on MLM [46,47,48,49,50,51,17,52]. In the biomedical area, Sung et al [53] extended the work of Cao et al on a new dataset, bioLAMA, confirming their observations for biological knowledge.…”
Section: Related Workmentioning
confidence: 95%
See 1 more Smart Citation
“…Cao et al [45] showed that predictions from MLM are highly prompt-biased and that, while external context apparently helps the models, its mainly via type guidance or answer leakage. In follow-up works, many domain-specific datasets and original prompting approaches were developed for factual knowledge extraction on MLM [46,47,48,49,50,51,17,52]. In the biomedical area, Sung et al [53] extended the work of Cao et al on a new dataset, bioLAMA, confirming their observations for biological knowledge.…”
Section: Related Workmentioning
confidence: 95%
“…Hallucinations tend to surface prominently in domain-specific discourse, including the sciences. This elicits the need to establish the ability of these models to encode and preserve factual knowledge as well as establishing methodologies for the critical evaluation of its representation properties [15,16,17].…”
Section: Introductionmentioning
confidence: 99%
“…Using LLMs for cell biology: Beyond the large-scale models tailored for structured, non-linguistic data, recent initiatives have explored the direct manipulations of LLMs for biomedically-focused tasks. For example, Hou and Ji [18] employed ChatGPT for cell type annotation; Wysocki et al [19] probed biomedical information on BioBERT and BioMegatron embeddings; and Ye et al [20] utilized instruction fine-tuning to achieve competitive results on graph data task benchmarks with an LLM. While our paper is under preparation, Levine et al [21] has independently embarked on a conceptually related approach to ours, where each cell is transformed into a sequence of gene names, ranked by expression level and truncated at top 100 genes.…”
Section: Related Workmentioning
confidence: 99%
“…This approach allows for more nuanced and dynamic representations. For example, Hou and Ji [21] employed ChatGPT for cell type annotation; Wysocki et al [22] investigated biomedical meanings encoded by BioBERT and BioMegatron embeddings; and Ye et al [23] utilized instruction fine-tuning to achieve competitive results on graph data task benchmarks with an LLM. Compared to prior works that directly query LLMs for biological tasks, our method solely utilizes the input descriptions of each gene (which can be sourced from high-quality databases such as NCBI [24]) and the embedding model of LLMs, which suffers less from problems such as hallucination.…”
Section: Using Language Models For Cell Biologymentioning
confidence: 99%
“…After pretrained models such as BERT [10], ALBERT [11], XLNet [12], and ELECTRA [13] are proposed, they have been widely employed in various NLP tasks [14][15][16][17]. Many researches employed NER and RE models based on pretrained models and achieved good results.…”
Section: Related Workmentioning
confidence: 99%